Lower habitual Intake of grains and protein groups associated with increasing the disease risk among Jordanians: A cross-sectional population-based study - Lana M. Agraib; Buthaina Alkhatib; Islam Al-Shami (Elsevier, 2024)
Background: Dietary habits have drastically and quickly altered worldwide, and this is a crucial modifiable factor affecting obesity prevalence, a risk factor for several non-communicable diseases. Aims: This study aims to illuminate Jordanians' dietary habits and their potential association with non-communicable diseases. Methods: This is a population-based cross-sectional study. A randomly selected sample of children, adolescents, adults, and older adults was invited to participate. Participants were categorized into two groups: those with diseases (diabetes, cardiovascular diseases, and their comorbidities) and those who had no diseases. A valid food frequency questionnaire was used to recall each food group's average daily number of portions. Results: The intake and percentage of recommendations from the groups that included fruits, cereals, and proteins were highest in the obese group. Disease-free individuals had the highest daily intake of proteins and grains, and a higher percentage of grains consumed. Compared to individuals without a condition (83.6 % and 57.6 %, respectively), participants with a disease were more likely to consume less protein (68.8 %) and grains (87.6 %) than the recommended amount. Less than the required amount of grain consumption raises the risk of disease by OR = 1.57 (95%CI: 1.05-2.34). The chance of contracting diseases is reduced when more grains are consumed than recommended (p-trend = 0.001). A lower-than-recommended protein intake doubled the risk of disease (OR = 2.08, 95%CI: 1.13-3.84). Conclusion: Obesity shifts habitual food toward more fruits, grains, and protein consumption. Grains and protein consumption less than recommendations were associated with increasing the risk of having disease.